Temperature effects on power characteristics of vertical-cavity surface-emitting lasers - Hisham, Hisham K.; Zainol Abidin, Nadiah Husseini; Alresheedi, Mohammed Thamer; Abas, Ahmad Fauzi; Ng, Khoon Eng; Mahdi, Mohd Adzir (American Scientific Publishers, 2024)
This paper presents a numerical study based on temperature dependency on Auger process, examining the impact of temperature change and laser cavity active region parameters on the output power characteristics (Pout) of vertical-cavity surface-emitting lasers (VCSELs). The active region parameters include active region diameter, effective length, active region thickness, injection current, and mirror reflectivity. With increasing temperature, Pout reduction rate rises in proportion to active region diameter growth as opposed to effective length or active region thickness growth. It was determined that Pout thermal effects change minimally with injection current variation but can be reduced or completely mitigated by increasing the mirror reflectivity. This study provides notable insights in the design of VCSEL with consideration of temperature dependency on the Auger process.